(untitled) (gjstudies, 2020)
This research investigates the complex and often paradoxical relationship between transparency initiatives and public sector accountability, challenging the prevailing assumption that increased information disclosure automatically leads to improved governance. While transparency is widely championed as a cornerstone ofaccountable government, its operationalization frequently yields unintended consequences, including information overload, performative compliance, and the erosion of deliberative space. This study proposes a novel analytical framework, theAccountability-Transparency Nexus (ATN), which reconceptualizes transparencynot as an end in itself but as a dynamic process whose value is contingent upon itsintegration with robust accountability mechanisms, civic capacity, and institutionaldesign. Through a mixed-methods approach combining computational analysis offreedom of information request outcomes, ethnographic case studies of participatory budgeting in three municipalities, and an experimental survey assessing citizeninterpretation of disclosed data, we uncover critical disconnects. Our findings reveal that raw data disclosure, absent contextual scaffolding and feedback loops, candiminish public trust and bureaucratic responsiveness. Conversely, strategically designed transparency, embedded within iterative citizen-state dialogue and coupledwith clear lines of answerability, significantly enhances perceived and actual accountability. The paper concludes that the future of effective transparency policylies in moving beyond the ’more is better’ paradigm towards intelligent, responsive,and relational transparency systems that empower rather than overwhelm, fosteringa culture of mutual accountability between the state and its citizens.